2007
DOI: 10.1139/t06-109
|View full text |Cite
|
Sign up to set email alerts
|

A hypoplastic constitutive model for clays with meta-stable structure

Abstract: A new hypoplastic model for clays with meta-stable structure is presented in this paper. A new method for incorporation of structure effects into hypoplastic models based on the modification of barotropy and pyknotropy factors is proposed and applied to an existing hypoplastic model for reconstituted clays. The new model is characterized by a simple calibration procedure and a small number of parameters. This makes the model particularly suitable for practical applications. The model is evaluated using experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 39 publications
2
26
0
Order By: Relevance
“…It is clear that the predictions of the modified model for tests on normally consolidated soils starting from the isotropic stress states are significantly different as compared to the original model. With parameters evaluated using drained tests the modified model captures well the soil behaviour under undrained stress paths, and its predictions are very similar to the model by Huang et al in [8] with slightly increased value of the parameter j * (Table 1) and n = 0.6 are shown in Fig. 10a, b.…”
Section: Isotropic Stress Statesupporting
confidence: 74%
“…It is clear that the predictions of the modified model for tests on normally consolidated soils starting from the isotropic stress states are significantly different as compared to the original model. With parameters evaluated using drained tests the modified model captures well the soil behaviour under undrained stress paths, and its predictions are very similar to the model by Huang et al in [8] with slightly increased value of the parameter j * (Table 1) and n = 0.6 are shown in Fig. 10a, b.…”
Section: Isotropic Stress Statesupporting
confidence: 74%
“…[15,20,25,26,28,31,44,45], or the CLoE-model [6,27]. We use hypoplasticity with intergranular strain [31] to test the performance of the numerical schemes proposed.…”
Section: Constitutive Models Of the Rate Typementioning
confidence: 99%
“…The incorporation of structure into hypoplastic model has been discussed in detail by Mašín (2007). In this context, the size of the SBS for unsaturated soils is controlled by the isotropic virgin compression line with the formulation according to Butterfield (1979) …”
Section: Model For Constant Suctionmentioning
confidence: 99%
“…For ln(s/s e ) < 0 (saturated state) N (s) = N and λ * (s) = λ * . It is, however, emphasized that the general formulation of the model can accommodate any other more complex relationships between N (s), λ * (s) and s. Mašín (2007) demonstrated that incorporation of variable virgin compressibility and the intercept N (s) into the hypoplastic model requires a modification of both barotropy and pyknotropy factors f s and f d in (1), which are now calculated in terms of N (s) and λ * (s). The respective expressions are given in Mašín and Khalili (2007).…”
Section: Model For Constant Suctionmentioning
confidence: 99%
See 1 more Smart Citation